Studnia z późnej epoki brązu ze Szczodrzykowa koło Kórnika - Krzyszowski, Andrzej (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
In 2004 rescue excavations were carried out at the multicultural site 4 in Szczodrzykowo, near Kórnik, Poznań District (in advance of the construction of the local gas pipeline). Within the area of 1260m2 60 features were unearthed, including 16 of the Lusatian culture. Among the latter a whole circular timber lined well was discovered, consisting of three parts made of a burned trunk of an aldertree. The parts were supported with several timber pegs from the outside. The fragments of pottery discovered in the well represent the style of the Late Bronze Age and the period from HaC till HaC – HaD. The chronology of the feature was estimated also on the basis of the 14C dating (a piece of the timber provided a sample) and the achieved dates ranged between 836 and 771 BC.
A late Bronze Age well from Szczodrzykowo near Kórnik